Thoracoscopic excision versus radiofrequency ablation of the sympathetic chain as a treatment for palmar hyperhidrosis: comparative study - Mohamed Saber Mostafa; Mohammed Elsherbeny; Ahmed Abdelbarr; Sameh Abdelhay (SpringerOpen, 2020)
Abstract Background Hyperhidrosis is an excess sweat secretion. Various modalities of treatment exist for hyperhidrosis. Although medical treatment is the first line of treatment, its long-term outcome is not satisfactory. In this study, we compared the results of thoracoscopic excision with that of radiofrequency ablation of the sympathetic chain as a treatment of palmar hyperhidrosis. Results During the period from January 2014 to December 2017, 42 patients with palmar hyperhidrosis after failure of medical treatment presented to Departments of Pediatric Surgery and Neurosurgery, Faculty of Medicine. They were 26 males and 16 females. Their ages ranged between 11 and 42 years (mean 21.78 years). Twenty patients underwent thoracoscopic excision of the sympathetic chain (in Pediatric Surgery Department), while 22 patients underwent radiofrequency ablation of the sympathetic chain (in Neurosurgery Department). For the thoracoscopic sympathectomy group, the mean operative time was 27.39 min, the mean length of hospital stay was 24.78 h, the mean sweating scale decreased from 3.28 preoperatively to 1.33 1 year postoperatively, and the main postoperative complication was compensatory hyperhidrosis (40%). For the radiofrequency ablation group, the mean operative time was 55 min, the mean length of hospital stay was 20.64 h, the mean sweating scale decreased from 3.29 preoperatively to 1.57 1 year postoperatively, and the main postoperative complication was recurrence of hyperhidrosis (27%). Conclusion Thoracoscopic excision is more effective than radiofrequency ablation of the sympathetic chain in improving palmar hyperhidrosis. However, it has a higher risk of developing compensatory hyperhidrosis.